Adaptive significance of coat colouration and patterns of Sciuromorpha (Rodentia). Issue 3 (4th May 2017) - Ancillotto, Leonardo; Mori, Emiliano
Abstract : An analysis on the adaptive meaning of coat colouration and colour patterns in Sciuromorpha, a successful group within rodents, was carried out. We ran analyses with and without taking into account the phylogeny of Sciuromorpha, by building up a comprehensive phylogenetic tree based on the published literature, as well as by testing a number of hypotheses connecting coat colouration or patterns with eco-behavioural traits of this mammalian group. We found that coat characteristics in these rodents are mostly related to concealment, with associations between colouration/patterns and habitats where each species lives. Communication also seems to play a role in shaping colourations in Sciuromorpha, particularly concerning extremities, with conspicuous ear/face markings and tail patterns being associated with social species; a role for interspecific communication as an antipredatory strategy is also discussed for tail patterns. Thus, concealment seems to be the primary driving force shaping coat colours in Sciuromorpha, with social communication and regulation of physiological processes playing minor roles.